IDENTIFICATION OF BEST GENERAL COMBINERS FOR YIELD AND YIELD RELATED TRAITS IN MAIZE ( TED TRAITS IN MAIZE (Zea Mays Zea Mays L.) THROUGH POOLED SCORE TECHNIQUES POOLED SCORE TECHNIQUES - B. C. CHANDANA; S. K. DESHPANDE (The Bioscan, 2016)
The study comprised of 12 lines, six testers, 72 derived hybrids and three checks, these entries were evaluated for perse during kharif -2012. The data on yield related parameters were considered for estimation of combining abilities using WINDOSTAT v8.1 software. Identification of best general combiners based on pooled score technique is advantageous than simple gca values because it imply erroneous results that is, gca effects alone influenced by, unit of measurement of traits, higher and lower values of gca. To identify the best combiners we followed different methods and based on which, lines BM254 and BM24 were identified as excellent combiners for yield and yield related traits. Testers, BM59 and BM258 were assessed to be best general combiners, indicating their ability in transmitting additive genes in the desirable direction to their progenies. Similarly, among the hybrids, the cross BM52 x BM258 was found to be best specific combination for yield and yield related traits. Thus, we recommend the lines BM254, BM24, BM59 and BM258 as best general combiners and thus they may be used in development of synthetic population or may be pooled to derive superior inbreds and intern can be used as breeding material for improvement of grain yield.